White-light imaging with fractal zone plates - Furlan, Walter D; Saavedra, Genaro; Monsoriu, Juan A (Optics letters, 2007)
We report the achievement of the first images to our knowledge obtained with a fractal zone plates (FraZPs). FraZPs are diffractive lenses characterized by the fractal structure of their foci. This property predicts an improved performance of FraZPs as image forming devices with an extended depth of field and predicts a reduced chromatic aberration under white-light illumination. These theoretical predictions are confirmed experimentally in this work. We show that the polychromatic modulation transfer function of a FraZP affected by defocus is about two times better than one corresponding to a Fresnel zone plate.